A violência no contexto da saúde : o que é violência para os trabalhadores de saúde - Peixoto, Herlam Wagner (2007)
This study is a reflection of the concepts of the violence from the health care workers in the municipality of Vitória, Espírito Santo, Brazil. We use the qualitative social research approach. A semi-structured interview was performed with the objective to identify differences in the concept of violence between the health care workers looking for this concept on the context of health. The analysis was done using the following analytical categories: the concept of violence; responsibilities and actions of the professionals to deal with the violence; the comprehensive of violence as a public heath subject and the conceptions about how health care workers are involved and how their respond of this matter. The results show that Health care workers had difficulties to identify the violence and to approach it. By the others hand they believe that this theme can be incorporate in their day life work, although they point out the importance of training and support by the institutions board to bring this subject and to highlight the violence as a public health issue.